EVALUASI PENGELOLAAN DANA DESA (STUDI KASUS DESA ORAHILI TUMORI KECAMATAN GUNUNGSITOLI BARAT KOTA GUNUNGITOLI) - Zebua, Parta Junius; Ndraha, Ayler Beniah (LPPM Universitas Nias Raya, 2023)
The preparation, use, supervision and responsibility of assets provided by the central government to villages in a country is known as village fund management. The aim of this village fund is to expand development and government assistance to environmental networks. This research assesses village fund management with an emphasis on Orahili Tumori village. This research uses qualitative methods to gain an internal and external understanding of village fund management strategies and the components that influence their implementation. This study led to a comprehensive meeting with figures in Orahili Tumori village, including the village head, the village Consultative Body (BPD), community group pioneers, and village residents. The research results show that village fund management in Orahili Tumori village involves dynamic collaboration from various parties and runs with good systems and responsibility.